Magnetically modified in-situ N-doped Enteromorpha prolifera derived biochar for peroxydisulfate activation: Electron transfer induced singlet oxygen non-radical pathway. (December 2021) - Xiong, Sheng; Deng, Yaocheng; Gong, Daoxin; Tang, Rongdi; Zheng, Jiangfu; Li, Ling; Zhou, Zhanpeng; Su, Long; Liao, Chanjuan; Yang, Lihua
Abstract: Herein, in-situ N -doped Enteromorpha prolifera derived magnetic biochar (MBC) was prepared by loading Fe3 O4 . It can effectively activate peroxodisulfate (PDS) to degrade tetracycline (TC) and easy recycling. The removal rate of TC reached 87.2%, and its possible degradation pathway was revealed through a liquid chromatography-mass spectrometer. This work first proposes the mechanism of in-situ N -doping and Fe synergistic effect on PDS activation. Unlike the well-reported role of N doping in activating PDS, except for the edge pyridine N plays a significant role in the activation of PDS. After the load of Fe, the synergistic effect of Fe and graphite N induces a non-radical path dominated by singlet oxygen ( 1 O2 ) due to the excellent electron transfer function. Through chemical quenching experiment, electron spin detection, and electrochemical analysis, the mechanism of PDS activation by MBC was thoroughly investigate. This research will deepen the understanding of the mechanism of transition metals and carbon materials in synergistically driving PDS activation, and guide biochar-mediated PDS activation in environmental remediation. Graphical abstract: Image 1 Highlights: The important role of graphite N in the non-radical pathway was firstly proposed. The synergy of Fe and N -doping enhanced PDS activation was firstly proposed. The synergy improved electron transfer to induce 1 O2 . Using natural biomass to achieve environment conversation and resource recycling.